2017
DOI: 10.1038/s41598-017-10292-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteome and phosphoproteome analyses highlight the adherent population during Trypanosoma cruzi metacyclogenesis

Abstract: Trypanosoma cruzi metacyclogenesis is a natural process that occurs inside the triatomine vector and corresponds to the differentiation of non-infective epimastigotes into infective metacyclic trypomastigotes. The biochemical alterations necessary for the differentiation process have been widely studied with a focus on adhesion and nutritional stress. Here, using a mass spectrometry approach, a large-scale phospho(proteome) study was performed with the aim of understanding the metacyclogenesis processes in a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…The presence of multiple putative phosphorylation sites that are conserved in the C-terminal region of the ACs (including the catalytic domain) suggests that this region may be involved in regulation of AC activity [ 88 ]. In T. cruzi , a quantitative proteomic and phosphoproteomic analysis confirmed that the C-terminal region of an AC isoform upregulated during metacyclogenesis [ 88 ] possesses 6 phosphorylation sites [ 89 ], which are partially conserved among the different T. brucei AC isoforms and may play a role in modulation of AC activity. A similar feature has been described for the kinase homology domain of NPR-A GC [ 90 ].…”
Section: T Brucei Camp Signaling Pathway: Frommentioning
confidence: 99%
“…The presence of multiple putative phosphorylation sites that are conserved in the C-terminal region of the ACs (including the catalytic domain) suggests that this region may be involved in regulation of AC activity [ 88 ]. In T. cruzi , a quantitative proteomic and phosphoproteomic analysis confirmed that the C-terminal region of an AC isoform upregulated during metacyclogenesis [ 88 ] possesses 6 phosphorylation sites [ 89 ], which are partially conserved among the different T. brucei AC isoforms and may play a role in modulation of AC activity. A similar feature has been described for the kinase homology domain of NPR-A GC [ 90 ].…”
Section: T Brucei Camp Signaling Pathway: Frommentioning
confidence: 99%
“…However, we need to be cautious concluding TE activity in trypanosomatids based only on this type of data, since those reads could be only a transitory molecule resulting from global RNA expression. On the other hand, peptides from Gag-like protein were detected during the differentiation process from T. cruzi Dm28c noninfective epimastigotes into infective metacyclic trypomastigotes [68], a stronger sign of possible activity. In addition, we found potential encoding VIPER copies in some other species.…”
Section: Viper and Tate: Ancient Residents And Survivors Of Kinetoplamentioning
confidence: 98%
“…To detect VIPER activity in T. cruzi Dm28c, we analyzed the presence of RNA-seq reads and peptides from VIPER in results of published transcriptomic [67] and proteomic studies of this strain [68]. As most VIPER copies are annotated as hypothetical proteins, we retrieved all TriTrypDB gene IDs and UniProt IDs from VIPER copies and searched for them in the tables containing all genes and proteins identified in the studies using in-house Python code.…”
Section: Characterization Of Copiesmentioning
confidence: 99%
“…Schenkman and co-workers have recently developed the acetylome of T. cruzi, and showed that some cytosolic enzymes including antioxidant effectors were continuously acetylated and deacetylated; presumably as a control system for their enzymatic activity or protein-protein interaction (Moretti et al, 2018). Further, a large-scale phosphoproteome analysis study showed that antioxidant enzymes, TryR, TryS, and thiol-dependent reductase 1, are major targets of phosphorylation during the metacyclogenesis transition process (Marchini et al, 2011;Amorim et al, 2017). Thus, PTMs could have a key role in achieving a rapid regulation of antioxidants enzymatic activity as well as in stage-specific modulation of antioxidants expression.…”
Section: Possible Fine-tuning Mechanisms Of T Cruzi Antioxidant Systemmentioning
confidence: 99%